Bringing To Light The Characteristics And Difficulties Faced By Female Entrepreneurs In The Garment Industry In The Pursuit Of Sustainable Production - Areola, PhD HSG, Eunice Mareth Querol; Natividad, Merlin B; Estebal, Ma. Elena C (Journal of Sustainable Community Development (JSCD), 2024)
The study explored the attributes and challenges faced by Filipino women entrepreneurs in the garment business who have been operating for at least 5 years in select cities in the Philippines. The research aimed to determine the entrepreneurs' attributes, problems and challenges they face, and use the findings to create an entrepreneurial model for business success. The attributes of the women entrepreneurs differed based on factors like age, years in business, marital status, number of children, education level, and whether they dreamed of being an entrepreneur as a child. There were significant differences in their personality traits, goal orientation, appreciation of support networks, and socially responsible attributes when considering these demographic factors. The respondents viewed issues like balancing work/family, risk aversion, negotiation skills, male discrimination, lack of family support and financial constraints as neutral challenges. However, their socially responsible attributes were linked to self/family/social problems, while goal orientation related to marketing/mobility issues. Most respondents considered themselves successful or very successful business owners. The proposed entrepreneurial model emphasizes that successful women entrepreneurs must have: a positive personality, goal orientation, appreciation for networking/teamwork, adherence to ethical practices, responsibility to society/environment, and the ability to balance work/life commitments. The recommendations include strengthening continuing education for entrepreneurs, disseminating information on government support programs, and enhancing gender equality in business lending from banks.